2016
DOI: 10.1051/0004-6361/201628853
|View full text |Cite
|
Sign up to set email alerts
|

The small-scale HH34 IRS jet as seen by X-shooter

Abstract: Context. Atomic jets are a common phenomenon among young stars, being intimately related to disk accretion. Most studies have been performed on jets from pre-main sequence stars. However, to date very little detailed information has been gathered on jets from young embedded low mass sources (the so-called class I stars), especially in the inner jet region. Aims. We exploit a diagnostic analysis based on multiwave spectroscopic observations to infer kinematics and physical conditions of the inner region of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The log(L [O i]HVC ) vs. logṀ acc correlation is particularly useful to indirectly estimate the mass accretion rate in moderately embedded sources driving jets, where the permitted lines or the LVC emission region might be subject to large extinctions or scattering (e.g. Nisini et al 2016).…”
Section: Correlation With Stellar and Accretion Parametersmentioning
confidence: 99%
“…The log(L [O i]HVC ) vs. logṀ acc correlation is particularly useful to indirectly estimate the mass accretion rate in moderately embedded sources driving jets, where the permitted lines or the LVC emission region might be subject to large extinctions or scattering (e.g. Nisini et al 2016).…”
Section: Correlation With Stellar and Accretion Parametersmentioning
confidence: 99%
“…Optical high-resolution observations of CTT stars have mainly addressed the kinematic properties of the [O i]630 line or performed a diagnostic analysis based on very few lines and exploiting a limited diagnostic range (e.g., Fang et al 2018, Banzatti et al 2019). On the other hand, recent VLT/X-shooter observations have shown the potential of combining several diagnostic forbidden lines in the optical and infrared (IR) ranges to constrain the physical properties of the emitting gas associated with the jets (Bacciotti et al 2011, Giannini et al 2013, Nisini et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the measurement of the depletion degree in the different velocity components is crucial to shed light on jet formation, as it depends upon both the location of the launching region and the ability of the jet to destroy the dusty disk material. Several observations have indicated that a significant degree of dust depletion occurs in the jet region close to the disk (e.g., Nisini et al 2005, Podio et al 2006, Giannini et al 2013, and that the depletion might decrease with jet velocity (Agra-Amboage et al 2011, Nisini et al 2016), suggesting that high-velocity jet channels preferentially originate in dust-free disk regions.…”
Section: Introductionmentioning
confidence: 99%
“…Because the bolometric temperature is not much higher than the Class 0/I boundary (70 K), the age of this protostar may be somewhat older than the typical lifetime of the Class 0 phase (∼10 5 years; Evans et al 2009). The prominent HH 34 jet has been studied extensively (Reipurth et al 1986(Reipurth et al , 2002Rodríguez & Reipurth 1996;Nisini et al 2016). The jet extends to a parsec-scale outflow that has a dynamic age of ∼10,000 years (Bally & Devine 1994;Devine et al 1997).…”
Section: Appendix Individual Dense Coresmentioning
confidence: 99%